2021
DOI: 10.1007/s00406-021-01277-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of body-oriented yoga: a RCT study for patients with major depressive disorder

Abstract: The major depressive disorder is one of the most common mental illnesses worldwide. Current treatment standards recommend a combined therapy with medication and psychotherapy. As an additive component and to further improvements in treatment, physical activity such as yoga may be integrated into conventional treatment. This study investigates the impact of a 3-month body-oriented yoga in patients with major depressive disorder (MDD). In total, n = 83 patients were included. An intervention group received a vig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 59 publications
(79 reference statements)
2
18
0
Order By: Relevance
“…Overall, changes in emotions require longer-term treatments [36]. This finding is consistent with the reports of Bieber et al (2021) [48], who also reported improvements in depression symptoms, but not in positive or negative emotions, after psychotherapy. Also, the analysis of treatment processes in an effort to open the black box of imagery-based cognitive therapy by the hermeneutic method revealed that processes such as triggering motivation to try, becoming aware of negative thoughts and emotions, being kind to oneself, coping with negative thoughts, formation of positive emotions, reducing negative emotions, and acquiring a better feeling about others played a role in the patient"s changes.…”
Section: Discussionsupporting
confidence: 87%
“…Overall, changes in emotions require longer-term treatments [36]. This finding is consistent with the reports of Bieber et al (2021) [48], who also reported improvements in depression symptoms, but not in positive or negative emotions, after psychotherapy. Also, the analysis of treatment processes in an effort to open the black box of imagery-based cognitive therapy by the hermeneutic method revealed that processes such as triggering motivation to try, becoming aware of negative thoughts and emotions, being kind to oneself, coping with negative thoughts, formation of positive emotions, reducing negative emotions, and acquiring a better feeling about others played a role in the patient"s changes.…”
Section: Discussionsupporting
confidence: 87%
“…The age of participants ranged between 19 and 76 years old. Fifty-six studies (1510 participants) examined the effects of AE [ 34 , 36 38 , 57 59 , 61 , 64 , 66 , 67 , 69 72 , 74 78 , 85 , 86 , 88 96 , 98 , 101 , 102 , 106 , 107 , 109 , 111 , 112 , 114 , 118 , 121 , 122 , 124 , 136 138 , 141 , 147 , 150 , 155 158 , 160 , 164 ], while 9 studies (161 participants) evaluated RE [ 57 , 60 , 63 , 70 , 122 , 125 , 134 , 149 , 166 ], 49 studies (1530 participants) evaluated MBE [ 35 , 43 , 62 , 73 , 79 – 84 , 87 , 93 , 97 , 99 , 100 , 103 – 105 , 110 , 115 117 , 119 , 120 , ...…”
Section: Resultsmentioning
confidence: 99%
“…A total of 36 studies directly investigated the treatment effects on mental health symptoms of AE vs. control condition [ 34 , 36 , 58 , 59 , 61 , 64 , 67 , 69 , 71 , 72 , 74 – 77 , 85 , 86 , 88 91 , 94 96 , 98 , 101 , 106 , 107 , 112 , 114 , 118 , 121 , 124 , 137 , 156 , 158 , 160 ], while 36 studies evaluated MBE vs. the control [ 35 , 43 , 62 , 73 , 79 – 84 , 87 , 97 , 99 , 100 , 103 – 105 , 110 , 115 117 , 119 , 120 , 123 , 126 131 , 142 , 144 , 152 , 153 , 161 , 162 ], 5 studies evaluated RE vs. the control [ 60 , 63 , 125 , 134 , 149 ], 9 studies evaluated ME vs. the control [ 39 , 65 , 108 , 113 , ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Furthermore, 14 studies reported multiple measures of depression for each participant. 25,28,35,39,65,76,96,99,113,114,119,135,138,154 For each of these studies, the measure-specific effect sizes were averaged to obtain one combined effect size per study as recommended in the literature. 15 The variance of the combined effect size for these studies increases as the within-subject correlation between different measures of depression, r 2 , increases.…”
Section: Statistical Proceduresmentioning
confidence: 99%